2007
DOI: 10.2341/06-104
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of C-factor, Flexural Modulus and Viscous Flow on Gap Formation in Resin Composite Restorations

Abstract: SUMMARYThis study analyzed the influence of C-factor, flexural modulus and viscous flow on gap formation in resin composite restorations. Two resin composites, a mini-filled hybrid (P 60) and a nanofilled (Supreme), were used. The flexural modulus was obtained from bar-shaped specimens submitted to three-point bending. Viscous flow was obtained from the difference between the initial and final diameter of resin composite disks submitted to a load of 10 N for 120 seconds. Gap analysis was conducted in three typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 30 publications
2
21
0
1
Order By: Relevance
“…34,35 In this study, the results demonstrated that water storage could significantly affect the mean coronal microleakage at the metal-ceramic/composite interface; there was a slight decrease in mean coronal microleakage in 7-day water storage compared to 1-day water storage. These slight differences could be explained by the slightly more water at 7 days than 1 day with more hygroscopic expansion, thereby agreeing with other studies that showed that the degree of hygroscopic expansion in resin-based composites had an inverse relationship between filler loading and water sorption, 45 thus compensating for resin composite shrinkage.…”
Section: Discussionsupporting
confidence: 90%
“…34,35 In this study, the results demonstrated that water storage could significantly affect the mean coronal microleakage at the metal-ceramic/composite interface; there was a slight decrease in mean coronal microleakage in 7-day water storage compared to 1-day water storage. These slight differences could be explained by the slightly more water at 7 days than 1 day with more hygroscopic expansion, thereby agreeing with other studies that showed that the degree of hygroscopic expansion in resin-based composites had an inverse relationship between filler loading and water sorption, 45 thus compensating for resin composite shrinkage.…”
Section: Discussionsupporting
confidence: 90%
“…The flow characteristics of a restorative material affect its ability to adapt to the walls of a cavity preparation. Thus, a composite resin with a higher flow might adapt more easily the walls of a cavity preparation than one with lower flow values [ 25 ]. Many studies have recommended preheating of conventional composites instead of the use of a flowable composite liner.…”
Section: Discussionmentioning
confidence: 99%
“…A low viscosity of these composites during the working period is also desirable as it can facilitate their injection into the root canal through the delivery devices, and for effective impregnation of dentinal substrates and post surface [25]. It also reduces the polymerisation shrinkage stress within the material during early setting [26,27] and the stress relief via resin flow relaxation can reduce the possibility of gap formation [14] and marginal leakage [28,29], which can enhance the longevity of the restorations. It has also been reported that the lower viscosity resin composites provide significantly higher adhesion to post surface attributed to higher intrusion on the substrates [8].…”
Section: Discussionmentioning
confidence: 99%
“…The higher viscosity that is associated with higher filler load [11] also impedes the injection of the material into the root canal producing gaps and voids that may provide a site for recurrent caries to develop. The composition of the matrix [12] also has an effect on both viscoelastic and rheological properties, which influence the contraction stress and microleakage of the direct restoration [13,14].…”
Section: Introductionmentioning
confidence: 99%